Consumption and shifting temporalities of daily life in times of disruption: undoing and reassembling household practices during the COVID-19 pandemic. Issue 1 (9th December 2022) - Greene, Mary; Hansen, Arve; Hoolohan, Claire; Süßbauer, Elisabeth; Domaneschi, Lorenzo
Abstract: The way in which time is produced and consumed during everyday life has crucial implications for sustainable consumption. Social practice approaches in particular have directed attention to the intersection of personal and collective temporalities as important for the patterning of everyday consumption. This article examines the temporal dynamics of daily practice-arrangement bundles experienced in "locked down" households in Germany, Ireland, Italy, Norway, and the UK during the COVID-19 pandemic. Drawing on 97 in-depth interviews with participants in all five countries, we investigate quotidian experiences of the breaking and (re-)making of daily routines in response to the pandemic. In doing so, we explore and document the temporal processes by which daily practice-arrangement bundles become undone, reassembled, and reconfigured. Our analysis reveals the institutional ordering of temporal relations between practices in terms of how they hang together, synchronize, or compete for householders' time. Giving particular attention to socially differentiated lockdown experiences, we analyze how disruption-induced changes to social institutions and systems of provision impact the hanging together of daily practice-arrangement bundles and the strategies employed to restructure and rebundle them in unequal ways. We further consider varied experiences in temporal reorganizations of daily life that support sustainable consumption of food and mobility and reflect on the implications of the analysis for sustainability governance. UF0001